Acromioclavicular Joint Repair Utilizing a Button Technique for Chronic Instability: A Case Report - Akbar Azizi Wijaya; Romy Deviandry; Ghuna Arioharjo Utoyo (Medicinus, 2025)
Background: Chronic acromioclavicular (AC) joint injuries are common in individuals engaged in overhead sports, resulting in persistent pain and functional limitations. This report presents a successful case of chronic AC joint injury repair using a button technique in a 26-year-old female patient, discussing the efficacy of this novel approach. Case Description: A 26-year-old female presented with a two-year history of right shoulder pain and instability following a fall during a sporting event. Despite conservative treatments, including physical therapy and corticosteroid injections, her symptoms remained unresolved, culminating in a constant pain level of 7/10 on a Visual Analog Scale (VAS) with significant impairment in daily activities. On clinical examination, tenderness over the AC joint, a prominent distal clavicle, and restricted range of motion (especially abduction) were observed. Radiographic imaging confirmed a chronic Type III AC joint injury. The patient opted for surgical intervention. Under general anesthesia, a horizontal skin incision was made over the AC joint. The joint surfaces were prepared, and the AC joint was reduced. A biodegradable button was positioned through drill holes in the acromion and the distal clavicle, securing the joint. The surgery concluded with soft tissue closure and a sterile dressing application. Postoperatively, the patient was immobilized in a sling for four weeks, followed by a structured rehabilitation program. At the 6-month follow-up, the patient reported significant pain reduction (VAS score of 2) and was able to resume all pre-injury activities, achieving a Constant-Murley score of 85—indicating a marked improvement in shoulder function. Conclusion: The button technique for repairing chronic AC joint injuries offers a minimally invasive option with promising outcomes in terms of pain relief and functional restoration. This case underscores the technique's potential as a reliable approach for similar injuries in young active individuals. Further studies are necessary to compare this method with traditional surgical techniques and to evaluate long-term outcomes.